The impact of legislation in the urban architectural identity - Salem Street in the Sulaymaniyah city as a case study - Hassan, Niaz Hussain (Sulaimani Journal for Engineering Sciences, 2016)
Most countries suffering in the world of the problem of pluralism in the aspects of architecture, and since the architecture is the physical product of human thought and human thought is changing, so the architecture reflects all the intellectual changes, and is a form of architectural virtual aspect of the architecture and the body most Highlighting the expression of architectural identity, where not can read architectural identity and a clear and distinct in the local architecture in the city of Sulaymaniyah by the shapes and exotic elements and random and non-correlated in architectural facades in the local architecture, Since the urban the urban legislation that have been developed for the organization and construction of architecture in the city have been altered and changed more than a dozen times since 2000 has affected in architectural form of local architecture and is one of the most important reasons for this phenomenon, and this vocabulary was the main topic in this research, especially urban legislation prevailing in the city and how to apply them in the local architecture, the results showed that the comprehensiveness of the instructions for the granting of licenses buildings and non-entry into the architectural details of the general qualities of identity architectural and how to carry out those instructions and follow-up by the municipality have a profound impact in the phenomenon of pluralism and indiscriminate in architecture.
Keywords: architectural identity; urban legislation; architectural form; Sulaymaniyah city